Proceedings of the 7th International Conference on Mobile and Ubiquitous Multimedia 2008
DOI: 10.1145/1543137.1543155
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of read performance for RFID-based mobile sensor data gathering applications

Abstract: We consider RFID-based sensing applications enabled by passive or semi-passive tags and mobile devices equipped with readers. We experimentally investigate the feasibility of such RFID-based mobile sensor data gathering applications, focusing on UHF RFID devices and indoor scenarios. We examine the impact of various factors, including reader mobility, multiple closely located tags and other key related metrics. Our measurement results suggest the feasibility of using RFID for such applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…A similar inference has been drawn in [9] and [11] wherein the authors suggested defining read range as the range in which a pre-defined read rate or accuracy of reading a tag can be achieved.…”
Section: Sensitivity To Deployment Environmentmentioning
confidence: 63%
See 1 more Smart Citation
“…A similar inference has been drawn in [9] and [11] wherein the authors suggested defining read range as the range in which a pre-defined read rate or accuracy of reading a tag can be achieved.…”
Section: Sensitivity To Deployment Environmentmentioning
confidence: 63%
“…Hence it is very important to understand the effect that the tags have on each other. The effect of proximity of the other tags to the read range and read accuracy is experimentally analyzed in [11] and [4]. The presence of multiple tag antennas in close range alters the current distribution, the radiation pattern and introduces mutual impedance.…”
Section: Effect Of Tags In Proximity To Each Othermentioning
confidence: 99%
“…[18][19][20][21][22] We extracted from that material all publicly available codes that fit the categories of the proposed class library. In many cases, the original code was available only in Java or only in C/C++.…”
Section: Library Of Code Snippets For the Generation Of Synthetic Promentioning
confidence: 99%
“…When the test operation is completed, the metrics are collected and stored (lines [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Figurementioning
confidence: 99%
“…It should be noted that RSSI values usually range from 0 dBm to -110 dBm as per manufacturers' specifications. Effects of different tag and antennae orientations on radio signals were also assessed in various studies, which mostly focused on the orientations of passive tags (Currie and Marina, 2008;Huang et al, 2008;Mello et al, 2008) and an antenna independently. Clarke et al (2006) evaluated the read rate of passive tags with different orientations and the materials that they were attached to.…”
Section: Introductionmentioning
confidence: 99%